Yang tai chi. For beginners [videorecording (DVD)] - Silver, David; Yang, Jwing-Ming, 1946- (YMAA Publication Center, 2012)
Tai Chi Chuan is a kind of moving meditation with ancient roots in Chinese martial arts. In this program, Dr. Yang, Jwing-Ming teaches you the traditional Yang-style form step-by-step, while explaining the meaning of each movement.